Kepemimpinan Pendidikan - Maulana, Ahmad Farhan; Fauzi, Anis; Zohriah, Anis (Peneliti.net, 2025)
This research aims to describe the concept of Educational Leadership in general, identify the characteristics of effective leadership in an educational context, and explore its impact on the quality of learning and student satisfaction. Educational leadership is a key element in achieving the goals of quality and inclusive education. In this research, various theories and models of educational leadership will be discussed to provide a comprehensive understanding of the roles and responsibilities of educational leaders.